1986
DOI: 10.1017/s0043174500066765
|View full text |Cite
|
Sign up to set email alerts
|

Weed Seed Demise in Soil in Weed-Free Corn (Zea mays) Production Across Nebraska

Abstract: An experiment was conducted at five locations in Nebraska to determine the extent of demise of weed seed in soil when seed production was eliminated from 1975 through 1979 in corn (Zea maysL.). Weed yields, weed seed production, and corn yields were determined under four weed management levels in 1980. Annual broadleaf weed seed were more prevalent than grass seed in cultivated soil throughout the study. The population of viable weed seed in soil declined 95% during the 5-yr period that weed seed production wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 12 publications
5
43
1
1
Order By: Relevance
“…Herbicides also can cause weed species shifts in agricultural fields (Roberts 1968). In a study by Burnside et al. (1986), the control of weeds by using herbicides did not eradicate the seeds of weed species from the soil seed bank.…”
Section: Resultsmentioning
confidence: 96%
“…Herbicides also can cause weed species shifts in agricultural fields (Roberts 1968). In a study by Burnside et al. (1986), the control of weeds by using herbicides did not eradicate the seeds of weed species from the soil seed bank.…”
Section: Resultsmentioning
confidence: 96%
“…A rapid increase in weed seed density of the dominant species can be expected when weeds are allowed to produce seed or left unchecked (5,7). In our study we observed this pattern only for common lambsquarters (Fig.…”
Section: Effects Of Weed Control Programs Applied In Corn/sugarbeet Amentioning
confidence: 99%
“…Once contaminated, the soil seed bank can allow regular recruitment and facilitate long‐term persistence of major infestations of grass weeds despite intensive management (Burnside et al . ), compromising the success of restoration efforts with native species (Grant & Koch ; Bayliss et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Propagule pressure and soil seed banks are a major driver for grass infestations in disturbed areas (Smith et al 2000;Bellairs et al 2006;Fensham et al 2013). Once contaminated, the soil seed bank can allow regular recruitment and facilitate long-term persistence of major infestations of grass weeds despite intensive management (Burnside et al 1986), compromising the success of restoration efforts with native species (Grant & Koch 1997;Bayliss et al 2006 Managing the soil seed bank to avoid establishment of weeds is a critical element for successful mining restoration in Australia (Mulligan 1996). However, current management plans for Gamba Grass focus on control of mature plants through the application of the 'knock-down' herbicide glyphosate, burning and slashing (NT Weed Management Branch 2018).…”
Section: Introductionmentioning
confidence: 99%